Finite element stress analysis to evaluate and compare the effect of splinting in periodontally compromised teeth having 55 % bone loss with different materials - Shivangi Joshi; Prakash Talreja; Prajakta Rao; Nilesh Joshi; Vinayak Thorat; Ruhi Mohta (Journal of Oral Biology and Craniofacial Research)
Background: Splinting is commonly employed to stabilize periodontally compromised teeth, but the choice of splint material significantly influences stress distribution within the periodontal ligament (PDL) and surrounding bone. This study aimed to evaluate and compare the stress distribution of four different splint materials—composite, fiber-reinforced composite (FRC), polyetheretherketone (PEEK), and metal—on mandibular anterior teeth with 55 % bone loss using finite element analysis (FEA). Methodology: Finite element models of mandibular anterior teeth with 55 % bone loss were developed using SOLIDWORKS 2020. Simulations were conducted for non-splinted teeth and for teeth splinted with composite, FRC, PEEK, and metal. Stress analysis was performed in ANSYS software under vertical (100N at 0°) and oblique (100N at 45°) loading conditions. Von Mises stress values in the PDL and cortical bone were recorded and statistically analyzed using MedCalc software to compare the performance of different splint materials. Results: Non-splinted teeth exhibited the highest stress levels, particularly under oblique loading conditions. Among the splinting materials, FRC showed the most effective reduction in stress across all teeth, especially under vertical loads. Composite and metal wire splints provided moderate stress reduction, with performance varying depending on the load angle. PEEK splints demonstrated good stress reduction under vertical loads but showed increased stress levels under oblique forces. These results underscore the influence of splint material and load direction on stress distribution in periodontally compromised teeth. Conclusion: The study highlights the critical role of splint material in reducing stress on the PDL of periodontally compromised teeth. FRC splints emerged as the most effective material for minimizing stress under both vertical and oblique loading conditions. Composite and metal wire splints offered moderate efficacy, while PEEK splints were less effective under oblique loads. These findings provide valuable insights for clinicians in selecting optimal splint materials for periodontal stabilization.